Uptake and Utilization of the Management of Anticoagulation in the Periprocedural Period App: Longitudinal Analysis - Spyropoulos, Alex C; Myrka, Anne; Triller, Darren M; Ragan, Stephen; York, Collin; King, Jaz-Michael; Lee, Ti-Kuang (JMIR Publications, 2018)
BackgroundAnticoagulants are major contributors to preventable adverse drug events, and their optimal management in the periprocedural period is particularly challenging. Traditional methods of disseminating clinical guidelines and tools cannot keep pace with the rapid expansion of available therapeutic agents, approved indications for use, and published medical evidence, so a mobile app, Management of Anticoagulation in the Periprocedural Period (MAPPP), was developed and disseminated to provide clinicians with guidance that reflects the most current medical evidence. ObjectiveThe objective of this study was to assess the global, national, and state-level acquisition of a mobile app since its initial release and characterize individual episodes of use based on drug selection, procedural bleeding risk, and patient thromboembolic risk. MethodsData were extracted from a mobile app usage tracker (Google Analytics) to characterize new users and completed episodes temporally (by calendar quarter) and geographically (globally, nationally, and in the targeted US state of New York) for the period between April 1, 2016 and September 30, 2017. ResultsThe app was acquired by 2866 new users in the measurement period, and the users completed nearly 10,000 individual episodes of use. Acquisition and utilization spanned 51 countries globally, predominantly in the United States and particularly in New York State. Warfarin and rivaroxaban were the most frequently selected drugs, and completed episodes most frequently included the selection of high bleeding risk (4888/9963, 49.06%) and high thromboembolic risk categories (4500/9963, 45.17%). ConclusionsThe MAPPP app is a successful means of disseminating current guidance on periprocedural anticoagulant use, as indicated by broad global uptake and upward trends in utilization. Limitations in access to provider and patient-specific data preclude objective evaluation of the clinical impact of the app. An ongoing study incorporating app logic into electronic health record systems at participant health systems will provide a more definitive evaluation of the clinical impact of the app logic.